(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Il contributo è destinato alla pubblicazione negli Atti del Convegno sul tema “Beni culturali di interesse religioso. Tutela ed esigenze di culto”, organizzato dall’Accademia nazionale di scienze lettere e arti di Modena e da Italia nostra, tenutosi a Modena il 17 maggio 2012. SOMMARIO: 1. La Costituzione culturale – 2. L’Accordo culturale - 3. Dalle esigenze di culto alle esigenze religiose – 4. L’armonizzazione della tutela – 5. La legificazione delle disposizioni armonizzate – 6. Il modulo procedimentale dell’accordo – 7. La differenza con gli accordi della p.a. con altri soggetti – 8. Implicazioni e limiti: a) delle esigenze religiose – 9. (Segue): b) delle esigenze di conservazione del patrimonio artistico – 10. Il principio di laicità come criterio di ripartizione delle competenze. ABSTRACT: The preservation of the cultural goods of religious interest according to the Italian Constitution and the Conventions with a few religious denominations According to the Italian Constitution the preservation of the cultural goods falls within the authority of the State. Yet, when these goods assume a religious importance, according to the conventions with a few religious denominations – among witch mainly the Catholic Church –, the competence is also of those Organizations. This paper aims to demonstrate that the notion of “religious reasons” is broader than “cult reasons” and therefore the authority of the State is more limited than in the past time. The Author maintains that the constitutional principle of laicity must act as guide-line about the competence disposition and illustrates this theory with particular reference to a leading case of liturgical modification of a cathedral. Keywords: cultural goods – religious interest – cult reasons - Italian Constitution – Catholic Church - laicity